The rhetorical function of the book of Ezekiel - Renz, Thomas. (Supplements to Vetus Testamentum,, 1999)
This study analyses the book of Ezekiel as a tool of communication, arguing that the book was designed to shape the self-understanding of the exilic community. A discussion of the historical context precedes a chapter that deals with the basic thrust and literary arrangement of Ezekiel. A detailed examination of individual rhetorical techniques (use of the watchman motif, legal traditions, emotional language, and others) and of crucial passages (especially 24:15-27 and 37:1-14) follows. The final chapter explores the book's suitability for the situation for which it was designed. This work gives readers the opportunity to study the book of Ezekiel as a whole and to explore some of its intricacies. Its methodology is an example of the fruitful integration of traditional critical methods and more recent literary and sociological approaches. This publication has also been published in paperback, please click here for details.